THE CORRELATION BETWEEN STUDENTS' READING FREQUENCYAND THEIR READING ABILTY:A Descriptive Study of Semester 6 Students of English Departmentof Indonesia University of Education - Lia Rosmalia, - (2008)
This study is aimed to investigate the correlation between students' reading frequency and their reading ability. It is assumed that there is a positive correlation between students' reading frequency and their reading ability. The population of the study is sixth semester students of English Department of UPI Bandung class of 2005. The sample observed was 30 students. The study used descriptive method with ex post defacto design. Itwas used to describe and investigate the existence of correlation between two different variables. Here the writer looked at the degree of relationship rather than at cause-and-effect relationship. Samples were asked to answer reading comprehension test and questionnaire. From the analysis, it was found that the distibution of the data from questionnaire and reading test are different each other in terms ofnormality. One of them is not normal, thus the writer analyzes further by using Spearman rank-order correlation rather than Pearson Product Moment correlation formula. The result shows that there is a high relationship between the ranks of students' reading frequency and their reading ability. And also since rs counted is greater than rs table so the writer can accept the alternative hypothesis. Here, the writer may say that there is a significant correlation between the two variables.